THE RELATION OF KNOWLEDGE LEVEL AND FARMERS’ ATTITUDE TOWARD THE MANAGEMENT OF THE IMPLEMENTATION OF PIGS MAINTANANCE AT KANATANG SUB DISTRICT, EAST SUMBA STATE - E. R. Raga Lay, Willnela; Suparta, I N.; Inggriati, N. W. T. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
Pig farming mostly done at Kanatang Sub District, East Sumba State, however the maintenance was inadequate. It made the productivity of pig farming was not optimal yet. The purpose of the research is to: 1) know the relation about the level of the knowledge and attitude of the farmer to the implementation of the pigs farming management at Kanatang Sub district; 2) knowthe level of the knowledge, attitude and the implementation of the pigs farming management at Kanatang Sub district. This research was conducted at Kanatang Sub district, East Sumba State. The respondent of this research was 50 persons which came from in Kanatang Sub district. The sample taking as the respondents used the method of “ Stratified Random Sampling” . The kind of data used in this research were primary and secondary data.The primary data obtained from direct interview and observatitio,the secondary obtained from the information existed in The Departement of Animal Husbandry of East Sumba. The analysis used in this research was qualitative analysis and Spearman level of correlation test. The result of the research showed that level of the pig farm maintenance at Kanatang Sub District include of the good category, the level of the farmers’ knowledge about the management of the pig farm include in high category, the attitude of the farmers about the management of the pig farm maintenance include in positive category. The factor of age and knowledge have the insignificant relation (P>0,10) with the level of pig farm maintenance management, while the farm owning and the attitude have significant relation (P<0,10) with the level of management implementation of pig farming, and knowledge have really significant relation (P<0,01) with the management implementation of pig farming at Kanatang Sub District. Key Word : Pigs, Management, Implementation, Knowledge, Attitude